Modelling and control for web real-time communication - Gaetano Carlucci; Luca De Cicco; Saverio Mascolo (53rd IEEE Conference on Decision and Control, 2014)
Congestion control for real-time media communication over the Internet is currently being addressed in IETF and W3C bodies aiming at standardizing a set of inter-operable protocols and APIs to enable real-time communication between Web browsers. In this paper we propose a mathematical model of the congestion control algorithm for real-time flows proposed by Google. Based on this model, we design a control algorithm that provides fair coexistence of real-time flows with TCP flows.
Keywords: Delays; Receivers; Detectors; Real-time systems; Mathematical model; Google; Kalman filters; Real-time communication; WebRTC; congestion control